2012
DOI: 10.1177/0734282912438869
|View full text |Cite
|
Sign up to set email alerts
|

The Factor Structure of the BASC-2 Behavioral and Emotional Screening System Teacher Form, Child/Adolescent

Abstract: The BASC-2 Behavioral and Emotional Screening System Teacher, Child/Adolescent Form (BESS Teacher Form C/A; Kamphaus & Reynolds, 2007) is a brief teacher-report rating scale designed to identify students who are at-risk for behavioral and emotional problems. The aim of this study was to describe the latent dimensions that underlie the responses to the BESS Teacher Form C/A. Exploratory factor analyses (EFA) and confirmatory factor analyses (CFA) across two random subsets of a nationally representative sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 16 publications
5
34
0
Order By: Relevance
“…Items are rated on a four-point scale ranging from 0 (never) to 3 (almost always), with higher scores indicating more problematic behavior. One study (Dever, Mays, Kamphaus, & Dowdy, 2012) has identified a possible fourfactor structure of the BESS; however, this has not been replicated and neither age-based T scores nor at-risk cutoff scores have been established for these subscales. Thus, the total score was used in this study.…”
Section: Basc-2 Behavioral and Emotional Screening System (Bess): Teamentioning
confidence: 99%
See 1 more Smart Citation
“…Items are rated on a four-point scale ranging from 0 (never) to 3 (almost always), with higher scores indicating more problematic behavior. One study (Dever, Mays, Kamphaus, & Dowdy, 2012) has identified a possible fourfactor structure of the BESS; however, this has not been replicated and neither age-based T scores nor at-risk cutoff scores have been established for these subscales. Thus, the total score was used in this study.…”
Section: Basc-2 Behavioral and Emotional Screening System (Bess): Teamentioning
confidence: 99%
“…Without assessment and treatment of both issues (SEB and early literacy), school professionals may only be providing supports for one of the problems (e.g., early literacy only), while SEB problems undermine the effects of literacyspecific interventions. Further, it is not surprising that the BESS is a stronger predictor of academic outcomes than the SDQ, as the BESS has eight items associated with school problems (Dever et al, 2012) and the SDQ has none. Similarly, given that the KRA-L measures readiness for concepts introduced early in the kindergarten year, it is not surprising that it accounts for more variance in firstquarter grades than fourth-quarter grades.…”
Section: Identifying and Predicting Academic Outcomesmentioning
confidence: 99%
“…In general, the School Problems, Inattention/Hyperactivity, Personal Adjustment, and Emotional Symptoms Index Composite scales were also found to measure their targeted sub‐domains. Although other studies have not examined model fit of the BASC‐2 SRP‐A (except for the initial BASC‐2 SRP‐A investigation), the related shortened form, called the Behavioral and Emotional Screening System Adolescent Form, was recently found to be associated with good model fit indices (Dever, Mays, Kamphaus, & Dowdy, ). The present results are thus consistent with those recently reported factor analytic findings.…”
Section: Discussionmentioning
confidence: 99%
“…The BASC-2 BESS is a screening tool developed to assess externalizing and internalizing behavior patterns, school problems, and adaptive skills (Dever, Mays, Kamphaus, & Dowdy, 2012; Dowdy, Chin, Twyford, & Dever, 2011; Kamphaus & Reynolds, 2007). Specifically, the BASC-2 BESS yields a comprehensive score of school adjustment and challenging behaviors.…”
Section: Methodsmentioning
confidence: 99%